Onshore Wind Farm Development: Technologies and Layouts - Francisco Haces-Fernandez; Mariee Cruz-Mendoza; Hua Li (Energies, 2022)
Significantly growing wind energy is being contemplated as one of the main avenues to reduce carbon footprints and decrease global risks associated with climate change. However, obtaining a comprehensive perspective on wind energy considering the many diverse factors that impact its development and growth is challenging. A significant factor in the evolution of wind energy is technological advancement and most previous reviews have focused on this topic. However, wind energy is influenced by a host of other factors, such as financial viability, environmental concerns, government incentives, and the impact of wind on the ecosystem. This review aims to fill a gap, providing a comprehensive review on the diverse factors impacting wind energy development and providing readers with a holistic panoramic, furnishing a clearer perspective on its future growth. Data for wind energy was evaluated by applying pivot data analytics and geographic information systems. The factors impacting wind energy growth and development are reviewed, providing an overview of how these factors have impacted wind maturity. The future of wind energy development is assessed considering its social acceptance, financial viability, government incentives, and the minimization of the unintended potential negative impacts of this technology. The review is able to conclude that wind energy may continue growing all over the world as long as all the factors critical to its development are addressed. Wind power growth will be supported by stakeholders’ holistic considerations of all factors impacting this industry, as evaluated in this review.